Students’ Perceived Barriers, Benefits & International Programmatic Preferences - Olivia C. Caillouet; Lisa S. Wood (Journal of International Agricultural and Extension Education, 2019)
Study abroad experiences can change college students by contributing to their development of self-awareness, communication skills, and ability to navigate the unknown. The objective of this study was to determine students’ perceived barriers, benefits, and preferences for international programs (IP). Undergraduate students in large-enrollment, required courses by major, and all freshman orientation undergraduate courses in Bumpers College were targeted and all grade classifications were represented (n = 672). Based on a five-point Likert-type scale (1 = completely disagree to 5 = completely agree), students reported “cost is too high” (M = 3.93, SD = 1.00) and being “too busy with school” (M = 3.54, SD = 1.10) as the barriers keeping them from participating in an IP. Using the same Likert-scale, students reported “socially/culturally learn more about a host country” (M = 4.61, SD = 0.67) and “life-changing opportunity” (M = 4.60, SD = 0.66) as the most influencing benefits. Students were most interested in short-term, faculty-led programs (n = 234, 27.2%) with a length of two to three weeks (n = 224, 30.7%) during summer session I (n = 307, 39.4%). Students reported they would like to learn more information about future IPs through email (n = 278, 34.8%), classroom visits (n = 111, 13.9%), and their academic advisors (n = 108, 13.5%). Assessing student’s barriers, benefits, and preferences for IPs will guide Bumpers College program development. It is important to focus IP efforts on students’ needs and interests, while also providing meaningful, engaged learning in all environments.
Keywords: agricultural education; barriers and benefits; international programs; study abroad